Evaluation of a modified sutureless technique for scleral fixation of one-piece posterior chamber intraocular lens: a retrospective study - Johari, Mohammadkarim; Attar, Alireza; Eghtedari, Dorna; Razavizadegan, Seyed Ahmad (Frontiers in Medicine, 2025)
BackgroundThis study presents the one-year outcomes of a modified technique for transscleral suture fixation of a posterior chamber intraocular lens (PCIOL) in aphakic eyes.MethodsA retrospective chart review was conducted on 45 patients who underwent transscleral suture fixation of a foldable one-piece PCIOL through scleral pockets. Preoperative data and follow-up data for a minimum of 12 months were collected for all patients.ResultsThe mean preoperative and postoperative uncorrected distance visual acuity (UDVA) in LogMAR was 2.49 ± 0.54 and 0.54 ± 0.25, respectively (p < 0.01). The mean preoperative and postoperative best-corrected visual acuity (BCVA) in LogMAR was 0.52 ± 0.22 and 0.45 ± 0.24, respectively (p < 0.01). The mean endothelial cell loss was 110.46 ± 11.5 cells/mm2. Postoperative complications included transient corneal edema (17.7%), transient elevated intraocular pressure (22.2%), and non-significant vitreous hemorrhage (11.1%). No severe complications were observed.ConclusionThe modified technique provides stable PCIOL placement in aphakic eyes with long-term follow-up.